THEOLOGY OF RELIGIONS - Kadankavil, Thomas (Journal of Dharma, 1989)
The scholarly studies and genuine search in the religious scriptures, traditions and the present practices to make the religions of the West and the East meet were for sometime centred around Comparative Study of Religions. At a later period the concern was for 'encounter' and 'dialogue.' Now we hear scholars and theologians speaking about developing a theology which would take into consideration the reality of the Plurality of Religions. In India this movement began with the effort of the theologians to develop an incultured or Indian Christian thology. The limitation in this attempt was immediately felt, that it would be a theology exclusively for Christians who are trying to accommodate their faith in the context of the plurality of religions. This would naturally lead one to the question whether there is any possibility of developing a theology, either valid for all existing religions equally or one which will take into consideration all existing-religions from the point of view of one particular religion. The fact is that the nascent discipline, The Theology of Religions, has not yet clearly defined to itself the scope of its investigation.